G-protein coupled receptor solubilization and purification for biophysical analysis and functional studies, in the total absence of detergent. Issue 2 (16th April 2015) - Jamshad, Mohammed; Charlton, Jack; Lin, Yu-Pin; Routledge, Sarah J.; Bawa, Zharain; Knowles, Timothy J.; Overduin, Michael; Dekker, Niek; Dafforn, Tim R.; Bill, Roslyn M.; Poyner, David R.; Wheatley, Mark
Abstract : It is universally acknowledged that exposing cell-surface receptors to detergent is detrimental. We have used a polymer to extract the receptor and surrounding lipid as a nanoparticle that provides a novel solution compatible with purification and receptor-based drug discovery assays. Abstract : G-protein coupled receptors (GPCRs) constitute the largest class of membrane proteins and are a major drug target. A serious obstacle to studying GPCR structure/function characteristics is the requirement to extract the receptors from their native environment in the plasma membrane, coupled with the inherent instability of GPCRs in the detergents required for their solubilization. In the present study, we report the first solubilization and purification of a functional GPCR [human adenosine A2A receptor (A2A R)], in the total absence of detergent at any stage, by exploiting spontaneous encapsulation by styrene maleic acid (SMA) co-polymer direct from the membrane into a nanoscale SMA lipid particle (SMALP). Furthermore, the A2A R–SMALP, generated from yeast ( Pichia pastoris ) or mammalian cells, exhibited increased thermostability (∼5°C) compared with detergent [DDM ( n -dodecyl- β -D -maltopyranoside)]-solubilized A2A R controls. The A2A R–SMALP was also stable when stored for prolonged periods at 4°C and was resistant to multiple freeze-thaw cycles, in marked contrast with the detergent-solubilized receptor. These properties establish the potential for using GPCR–SMALP in receptor-based drug discovery assays. Moreover, in contrast with nanodiscs stabilized by scaffold proteins, the non-proteinaceous nature of the SMA polymer allowed unobscured biophysical characterization of the embedded receptor. Consequently, CD spectroscopy was used to relate changes in secondary structure to loss of ligand binding ([ 3 H]ZM241385) capability. SMALP-solubilization of GPCRs, retaining the annular lipid environment, will enable a wide range of therapeutic targets to be prepared in native-like state to aid drug discovery and understanding of GPCR molecular mechanisms.